Determination of Heterocyclic Aromatic Amines (HAAs) in Urban Particulate Standard Reference Material and Wildfire-Influenced Particulate Matter by High-Performance Liquid Chromatography-Tandem Mass Spectrometry (HPLC-MS/MS). (13th October 2022) - Miller-Schulze, Justin P.; Dal Porto, Rachael; Fagundes, Ashley; Oanh Pham, Kim; Olson, Michael; Schauer, James J.
Abstract: Heterocyclic aromatic amines (HAAs) are carcinogenic and mutagenic compounds formed by the cooking of meat and combustion of biomass. There are relatively few data on HAAs in atmospheric particulate matter (PM). We developed an analytical method using high performance liquid chromatography – tandem mass spectrometry (tandem quadrupole, HPLC-MS/MS(QqQ)) to analyze PM samples for 12 HAAs. We applied this method to an urban air standard reference material and wildfire-impacted PM2.5 from the 2018 wildfire season in Northern California. The PM sample matrix adversely impacted the MS/MS response, with high levels of ion suppression for sample masses >4 mg and higher ion suppression in wildfire-impacted particulate matter compared with the standard reference material. Despite detection limits at the low ng level, no HAAs were detected in the standard reference material, but β-carboline norharman (0.34 ng/m 3 ) was detected in one wildfire sample.